2012
DOI: 10.1099/jmm.0.037978-0
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Staphylococcus aureus USA300 protein signature using matrix-assisted laser desorption/ionization time-of-flight mass spectrometry

Abstract: Staphylococcus aureus strain type USA300 is an important human pathogen. Matrix-assisted laser desorption/ionization time of flight (MALDI-TOF) mass spectrometry has been used successfully for rapid identification of S. aureus at the genus and species levels. Here, it was hypothesized that MALDI-TOF could be used to identify USA300 organisms at the strain level. A genetic algorithm model using ClinProTools software (Bruker Daltonics) was built using 47 isolates of USA300 S. aureus and 77 non-USA300 S. aureus i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 23 publications
0
20
0
1
Order By: Relevance
“…Among the three model generation algorithms available, models based on the genetic algorithm performed better for our study isolates than the other algorithms (Supervised Neural Network and QuickClassifier; data not shown). Two recent studies have used classification models generated using ClinProTools software for distinguishing between two Staphylococcus aureus strains (22) and between Streptococcus pneumoniae and S. mitis (23). The genetic algorithm was either the optimal algorithm for model generation or worked as well as the other options in both studies.…”
Section: Discussionmentioning
confidence: 99%
“…Among the three model generation algorithms available, models based on the genetic algorithm performed better for our study isolates than the other algorithms (Supervised Neural Network and QuickClassifier; data not shown). Two recent studies have used classification models generated using ClinProTools software for distinguishing between two Staphylococcus aureus strains (22) and between Streptococcus pneumoniae and S. mitis (23). The genetic algorithm was either the optimal algorithm for model generation or worked as well as the other options in both studies.…”
Section: Discussionmentioning
confidence: 99%
“…Another promising study using an UltraFlex III machine proposed three protein peaks as specific for 197 of 224 (88%) USA300 isolates (9). However, a previous study (7) identified one of the peaks, m/z 6,423, as species specific, while a second peak, m/z 6,592, was more generally associated with CC8, to which USA300 belongs.…”
mentioning
confidence: 91%
“…Indeed, it is possible to identify Listeria monocytogenes serotypes, Yersinia enterocolitica biotypes and Salmonella enterica subspecies (Barbuddhe et al, 2008;Stephan et al, 2011;Dieckmann et al, 2008). MALDI-TOF MS also differentiates some M types of Streptococcus pyogenes (Wang et al, 2012) and clonal complexes of Staphylococcus aureus (Wolters et al, 2011;Boggs et al, 2012). Recently MALDI-TOF MS has been successfully used for the identification of some pathovars of E. coli (Clark et al, 2013).…”
Section: Introductionmentioning
confidence: 98%